Hydrogen Variability in the Murray Formation, Gale Crater, Mars. Issue 9 (27th August 2020) - Thomas, N. H.; Ehlmann, B. L.; Rapin, W.; Rivera‐Hernández, F.; Stein, N. T.; Frydenvang, J.; Gabriel, T.; Meslin, P.‐Y.; Maurice, S.; Wiens, R. C.
Abstract: The Mars Science Laboratory (MSL) Curiosity rover is exploring the Murray formation, a sequence of heterolithic mudstones and sandstones recording fluvial deltaic and lake deposits that comprise over 350 m of sedimentary strata within Gale crater. We examine >4, 500 Murray formation bedrock points, employing recent laboratory calibrations for ChemCam laser‐induced breakdown spectroscopy H measurements at millimeter scale. Bedrock in the Murray formation has an interquartile range of 2.3–3.1 wt.% H2 O, similar to measurements using the Dynamic Albedo of Neutrons and Sample Analysis at Mars instruments. However, specific stratigraphic intervals include high H targets (6–18 wt.% H2 O) correlated with Si, Mg, Ca, Mn, or Fe, indicating units with opal, hydrated Mg sulfates, hydrated Ca sulfates, Mn‐enriched units, and akageneite or other iron oxyhydroxides, respectively. One stratigraphic interval with higher hydrogen is the Sutton Island unit and Blunts Point unit contact, where higher hydrogen is associated with Fe‐rich, Ca‐rich, and Mg‐rich points. A second interval with higher hydrogen occurs in the Vera Rubin ridge portion of the Murray formation, where higher hydrogen is associated with Fe‐rich, Ca‐rich, and Si‐rich points. We also observe trends in the H signal with grain size, separate from chemical variation, whereby coarser‐grained rocks have higher hydrogen. Variability in the hydrogen content of rocks points to a history of water‐rock interaction at Gale crater that included changes in lake water chemistry during Murray formation deposition and multiple subsequent groundwater episodes. Plain Language Summary: We measured the water content of bedrock targets in the Murray formation, a sequence of mudstones and sandstones part of Gale crater's Mt. Sharp, by applying recent laboratory calibrations to measurements from the Curiosity ChemCam instrument. While most rocks contained 2.3–3.1 wt.% H2 O, consistent with measurements by other Mars Science Laboratory instruments, we found some stratigraphic intervals contained high water content (6–18 wt.% H2 O) rocks including the Vera Rubin ridge. Based on our analysis of the corresponding major element composition, these are likely clays, Ca sulfates, Mn‐enriched units, and akageneite or other iron oxyhydroxides. The variation in water content indicates a history of water‐rock interaction at Gale crater that included changes in lake water chemistry during Murray formation deposition and multiple subsequent groundwater episodes. Key Points: Murray formation bedrock points measured by ChemCam have an interquartile range of 2.3–3.1 wt.% H2 O Specific intervals like the Vera Rubin ridge contain high H and indicate phases including iron oxyhydroxides, akageneite, and jarosite Variations in water content indicate changes in depositional lake water chemistry and multiple subsequent groundwater episodes